2016
DOI: 10.1097/mbc.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

Induction of endothelial cell proliferation and von Willebrand factor expression and secretion by leukemic plasma of patients with chronic lymphocytic leukemia before and after inhibition of NF-κB

Abstract: Although certain evidence has indicated a role for angiogenesis in the pathophysiology of hematopoietic malignancies, its role in chronic lymphocytic leukemia (CLL) prognosis is yet to be defined. To our knowledge, the effects of CLL plasma on cell culture have not been addressed. Therefore, we investigated the effects of CLL plasma on cell cycle regulation and von Willebrand factor (vWF) secretion, and expression in human umbilical vein endothelial cell cultures (HUVECs). Since nuclear factor-kappa B (NF-κB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…There are very few reports on angiogenesis in CLL [3,4]. It was shown that CLL plasma promotes vWF secretion, and expression in human umbilical vein endothelial cell cultures (HUVECs) [3] and microvessel density was found increased in CLL patients' bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports on angiogenesis in CLL [3,4]. It was shown that CLL plasma promotes vWF secretion, and expression in human umbilical vein endothelial cell cultures (HUVECs) [3] and microvessel density was found increased in CLL patients' bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found a proliferative effect of the CLL plasma together with vWF increased level in endothelial cell culture [10]. Accordingly, evaluation of cells overexpressing CD34 and VEGFR2, which are linked with angiogenesis and migration, seems to be valuable.…”
Section: Introductionmentioning
confidence: 98%